Evaluation of Lipid Profile among Combined Oral Contraceptive Pill Users Attending Two Tertiary Level Hospitals in Bangladesh (Journal of Comilla Medical College Teachers' Association, 2026)
Background: Contraceptives are devices or techniques used to prevent pregnancy. In Bangladesh combined oral contraceptives are most commonly used birth control measures which contain two hormonal components either oestrogen and progesterone or only progesterone. However, it is known that the combination of different substances in contraceptives may have different effects on lipid profile.Objectives: The objective of the study was to evaluate the lipid profile among combined oral contraceptive pill users attending two tertiary level hospitals of Bangladesh. Methods: This cross-sectional analytical study was carried out in the family planning clinic of Dhaka Medical College Hospital (DMCH), Dhaka and Shaheed Tajuddin Ahmad Medical College Hospital (STAMCH), Gazipur, Dhaka during July 2022 to June 2023. A total of 94 female participants of 18 to 45 years of age were included in this study by consecutive sampling technique. Among 94 participants, 47 participants using COCPs for 36 months considered as test group and rest 47 participants who did not use any hormonal contraceptives for last 36 months considered as control group. After taking informed written consent, 5 ml of fasting blood sample was collected for measurement of lipid profile of study participants. Then comparison of laboratory parameters with test group of the COCP users and control group was done.Result: There was a statistically significant (p